2015
DOI: 10.4172/2327-5162.1000193
|View full text |Cite
|
Sign up to set email alerts
|

Biofield Treatment: An Alternative Approach to Combat Multidrug-Resistant Susceptibility Pattern of Raoultella ornithinolytica

Abstract: Raoultella ornithinolytica is belongs to the family of Enterobacteriaceae, a Gram-negative encapsulated aerobic bacillus associated with bacteremia and urinary tract infections. As biofield therapy is increasingly popular in biomedical heath care, so present study aimed to evaluate the impact of Mr. Trivedi's biofield treatment on antimicrobial sensitivity, minimum inhibitory concentration (MIC), biochemical study, and biotype number of multidrug resistant strain of R. ornithinolytica. Clinical sample of R. or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…Antimicrobial interactions with S. marcescens might alter the ligand-receptor protein that results in different phenotypic characteristics [34]. Our research group has also reported significantly improved the sensitivity pattern of antibiotics after biofield treatment on pathogenic microbes [19,20], and inhibit the growth of cancer cells [35]. The results are very well supported with previous published literature.…”
Section: Antimicrobial Susceptibility Testsupporting
confidence: 85%
See 1 more Smart Citation
“…Antimicrobial interactions with S. marcescens might alter the ligand-receptor protein that results in different phenotypic characteristics [34]. Our research group has also reported significantly improved the sensitivity pattern of antibiotics after biofield treatment on pathogenic microbes [19,20], and inhibit the growth of cancer cells [35]. The results are very well supported with previous published literature.…”
Section: Antimicrobial Susceptibility Testsupporting
confidence: 85%
“…Specific environmental frequencies can be absorbed by biomolecules, and responding into the useful way that is called biofield energy and the process is known as biofield treatment. Mr. Trivedi's unique biofield energy is also known as The Trivedi effect ® , which has been effectively reported in the field of materials science research [12][13][14], agricultural research [15][16][17][18], and microbiology research [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Biofield Energy Healing Treatment (The Trivedi Effect ® ) has been published in numerous peerreviewed science journals due to its significant impacts in the science fields of biotechnology, genetics, cancer, microbiology, materials science, agriculture, and pharmaceuticals. These publications reported that Biofield Energy Treatment (The Trivedi Effect ® ) has the astounding capability to transform the physical, structural, chemical, thermal and behavioral properties of several pharmaceuticals [23,24], nutraceuticals [25,26], organic compounds [27][28][29][30], metals and ceramics in materials science [31][32][33], improve the overall productivity of crops [34][35][36], as well as modulate the efficacy of various living cells [37][38][39][40]. Although magnesium gluconate displays the highest bioavailability and moderate solubility in water in comparison to other magnesium salts, humans still face problems in achieving their daily requirements of magnesium [41].…”
Section: Introductionmentioning
confidence: 99%
“…To this day, Biofield Energy Healing has had significant impact in the transformation of living organisms and nonliving materials including metals, polymers, ceramics, chemicals, and pharmaceutical compounds. Even further, Biofield Energy Healing Treatment (The Trivedi Effect ® ) has been published in numerous peer-reviewed science journals due to its significant impacts in the science fields of biotechnology [15][16], genetics [17][18][19], cancer [20][21], microbiology [22][23][24][25][26], materials science [27][28][29][30], and agriculture [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%